Bleeding Patterns among Severe Hemophilia A and B Patients in West Java - Muhammad Mufakkirul Islam; Susi Susanah; Amaylia Oehadian (Althea Medical Journal, 2020)
Background: The clinical manifestations of hemophilia A (HA) and hemophilia B (HB)are quite similar; however, the bleeding characteristics of these two hemophilia types have been reported to be different. This study aimed to explore the bleeding patterns among patients with severe HA and severe HB.Methods: A cross-sectional study was conducted among patients with severe HA and HB registered at the West Java Indonesian Hemophilia Society. The inclusion criteria were patients with severe hemophilia diagnosed for at least one year. The bleeding patterns included bleeding episodes and bleeding types. The Mann-Whitney test was used to compare bleeding episodes and a chi-square test for bleeding types.Results: In total, 158 severe HA patients and 21 severe HB patients were included with a median bleeding frequency per patient per year for HA and HB was 24 (range 0–48) and 24 (range 5–48), respectively. The bleeding types in HA and HB were ecchymosis (69% vs. 66.7%), hematoma (62.7% vs. 61.9%), hemarthrosis (99.4% vs. 100%), epistaxis (46.8% vs. 38.1%), gum bleeding (87.3% vs. 95.2%), intracranial hemorrhage (15.2% vs. 9.5%), multiple hematomas (36.7% vs. 47.6%), hemarthrosis-hematoma (61.4% vs.61.9%), and hemarthrosis-ecchymosis (69% vs. 61.9%). However, there was no significant difference in all types of bleeding between HA and HB.Conclusions: There is no difference in the pattern of hemorrhage between severe HA and severe HB in West Java. However, the bleeding phenotypes in hemophilia has considerable implications in the therapeutic process. Further research is needed to optimize the treatment regimens.